الإغتراب النفسي وعلاقته بالتكيف الأكاديمي لطلاب الجامعة - عمارة، رمال, بن درويش، صبرينة (جامعة الوادي university of Eloued, 2017)
ملخص: تهدف الدراسة إلى الكشف عن طبيعة العلاقة التي تربط الاغتراب النفسي بالتكيف الأكاديمي لدى طلبة جامعة الشهيد حمه لخضر-الوادي، كما تسعى إلى الكشف الفروق عن ظاهرة الاغتراب النفسي في درجة التكيف الأكاديمي تبعا للمتغيرات التالية: الجنس، المستوى الدراسي، مكان الإقامة. وقد تمثلت الفرضية العامة للدراسة في: - توجد علاقة ارتباطية بين الاغتراب النفسي والتكيف الأكاديمي لدى طلبة الجامعة. وتتفرع منها الفرضيات الجزئية التالية: 1- توجد فروق ذات دلالة إحصائية في درجة الاغتراب النفسي لدى طلبة الجامعة تبعا لمتغير الجنس 2- توجد فروق ذات دلالة إحصائية في درجة التكيف الأكاديمي لدى طلبة الجامعة تبعا لمتغير الجنس. 3- توجد فروق ذات دلالة إحصائية في درجة الاغتراب النفسي لدى طلبة الجامعة تبعا لمتغير المستوى الدراسي. 4- توجد فروق ذات دلالة إحصائية في درجة التكيف الأكاديمي لدى طلبة الجامعة تبعا لمتغير المستوى الدراسي. 5- توجد فروق ذات دلالة إحصائية في درجة الاغتراب النفسي لدى طلبة الجامعة تبعا لمكان الإقامة. 6- توجد فروق ذات دلالة إحصائية في درجة التكيف الأكاديمي لدى طلبة الجامعة تبعا لمكان لإقامة. وقد تحددت الدراسة الحالية بالمنهج الوصفي، واختيرت العينة بطريقة عشوائية طبقية من جامعة الوادي، وقد اعتمدنا على أداتين لجمع البيانات حول متغيرات الدراسة وهي استبيان يقيس مستوى الاغتراب النفسي واستبيان يقيس مستوى التكيف الأكاديمي لدى طلبة الجامعة، كما اعتمدنا على الرزمة الإحصائية للعلوم الاجتماعية spss في تحليل البيانات. وكانت الاساليب الإحصائية المتبعة مقتصرة على اختبار "ت" لدلالة الفروق بين متوسطي عينتين مستقلتين، ومعامل ارتباط " بيرسون " وقد أسفرت نتائج البحث، عن وجود علاقة ارتباطية موجبة بين الاغتراب النفسي والتكيف الأكاديمي، مما يدل على أنه كلما قلت درجة الاغتراب النفسي كلما زاد ت درجة التكيف الأكاديمي لدى طلاب الجامعة والعكس. أما فيما يخص الفروق في الاغتراب النفسي والتكيف الأكاديمي وتبعا لمتغيرات التالية: الجنس، المستوي الدراسي، مكان الإقامة فقد توصلت النتائج إلى عدم وجود فروق ذات دلالة إحصائية في متغير الجنس، المستوى الدراسي، مكان الإقامة. Summary : The study aims at uncovering the nature of the relationship between psychological alienation and academic adjustment among the students of Chahid Hama Lakhedar University. He also seeks to uncover the differences in the phenomenon of psychological alienation in the degree of academic adjustment according to the following variables: gender, level of study, place of residence. The general hypothesis of the study was: _ There is a correlation between psychological alienation and academic adjustment among university students. The following partial hypotheses are derived: 1- There are statistically significant differences in the degree of psychological alienation among university students according to the gender variable. 2- There are differences of statistical significance in the degree of academic adaptation of university students depending on the gender variable. 3- There are differences of statistical significance in the degree of psychological alienation among university students depending on the variable level of study. 4- There are statistically significant differences in the degree of academic adjustment among university students according to the level of the academic level. 5- There are differences of statistical significance in the degree of psychological alienation among university students depending on the place of residence. 6- There are differences of statistical significance in the degree of academic adaptation of university students depending on the place of residence. The current study has been determined by the descriptive method, The sample was randomly selected from El-Oued University. We have relied on two tools to collect data on study variables, a questionnaire that measures the level of psychological alienation and a questionnaire that measures the level of academic adaptation of university students. We also relied on the statistical package of social sciences (SPSS) in data analysis. The statistical methods used were limited to the T test to indicate the differences between two independent sample averages and Pearson correlation coefficient. The results of the study revealed a positive correlation between psychological alienation and academic adjustment, indicating that the lower the degree of alienation, Degree of academic adaptation of university students and vice versa. As for the differences in psychological alienation and academic adjustment according to the following variables: sex, level of study, place of residence, the results found that there were no statistically significant differences in gender variable, level of study, place of residence.
دراسة ميدانية على عينة من طلاب جامعة الشهيد حمة لخضر الوادي
مذكرة ماستر في علوم التربية تخصص إرشاد وتوجيه
Keywords: الإغتراب النفسي، التكيف الأكاديمي; Aliénation psychologique, adaptation scolaire; Psychological alienation, academic adjustment